The Inspirations of the Tao Zhu-Gong modern business lessons from an ancient past - Wee, Chow Hou (Prentice Hall, 2001)
The Inspirations of Tao Zhu-gong: Modern Business Lessons from an Ancient Past discusses the 12 business principles of Tao Zhu-gong and relates them to today's corporate setting. They state 12 vital abilities that one will need in order to succeed in business. Ranging from handling customers and employees to managing a company and its products to making business decisions, the principles cover most of the areas necessary for a business to develop.